2006
DOI: 10.1124/dmd.105.008664
|View full text |Cite
|
Sign up to set email alerts
|

Quinacrine Is Mainly Metabolized to Mono-Desethyl Quinacrine by Cyp3a4/5 and Its Brain Accumulation Is Limited by P-Glycoprotein

Abstract: ABSTRACT:Quinacrine (QA), an antimalarial drug used for over seven decades, has been found to have potent antiprion activity in vitro. To determine whether QA can be used to treat prion diseases, we investigated its metabolism and ability to traverse the blood-brain barrier in mice. In vitro and in vivo, we identified by liquid chromatography-tandem mass spectrometry the major metabolic pathway of QA as N-desethylation and compared our results with an authentic reference compound. The major human cytochrome (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 23 publications
3
42
0
Order By: Relevance
“…First, the effects of "antiprion" compounds are clearly species/strain-dependent, in that drugs found to restrain prions in one situation may improve replicative ability in another. Based on initial reports of quinacrine's effects on mouse prion propagation in cell culture, a plethora of studies were designed to discern the mechanism of its presumed antiprion effects (19,20,(29)(30)(31)(38)(39)(40)(41)(42)(43)(44)(45), to assess its pharmacokinetics (21,36,42,46) and to derive similar compounds with improved antiprion efficacy (18,20,(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). These studies continue to this day, despite multiple failed clinical studies in patients with human prion diseases (10)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…First, the effects of "antiprion" compounds are clearly species/strain-dependent, in that drugs found to restrain prions in one situation may improve replicative ability in another. Based on initial reports of quinacrine's effects on mouse prion propagation in cell culture, a plethora of studies were designed to discern the mechanism of its presumed antiprion effects (19,20,(29)(30)(31)(38)(39)(40)(41)(42)(43)(44)(45), to assess its pharmacokinetics (21,36,42,46) and to derive similar compounds with improved antiprion efficacy (18,20,(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). These studies continue to this day, despite multiple failed clinical studies in patients with human prion diseases (10)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…and S.B.P., unpublished data). During studies of Qa metabolism in mice, we found that Qa efflux from the brain is controlled by multidrug-resistant (MDR) proteins, members of the P-glycoprotein ATP binding cassette transporters (22). Disappointingly, MDR-deficient mice accumulate high levels of Qa in their brains but fail to show prolonged survival after prion inoculation (K.G.…”
mentioning
confidence: 99%
“…For these 73 (Table 3). [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] The mean (± S.D.) and median CYP3A5/CYP3A4 ratios of the metabolic activities in these 47 reactions were 0.69 ± 1.23 and 0.28, respectively.…”
Section: Metabolic Activity Of Cyp3a4 and Cyp3a5mentioning
confidence: 99%